Radicalism and Intolerance in Padang City - Muhammad Faisal Hamdani; Eldin Zainal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Padang is a unique city because its people have the principle of making their customs code syara 'and syara' coded as Kitabullah in everyday life. This principle has always been the motivation to act and it is not uncommon for some Padang people to be accused of radicalism and intolerance. This article explores the development of radicalism and violence in the city of Padang according to research figures, scientists, community leaders and also some students and the general public. This article is taken from the results of our interviews with several figures of Islamic mass organizations in Padang, scientists and the community, both in person (face to face) and via smartphone communication such as the Chairman of the MUI, Gus Rizal.